Answer:
The explicit formula
[tex]a_n = 3 +0.25 (n-1)[/tex]
The recursive formula
[tex]a_1 = 3[/tex] for [tex]n=1[/tex]
[tex]a_n = a_ {(n-1)} +0.25[/tex] if [tex]n>1[/tex]
Step-by-step explanation:
If a sequence is arithmetical then the difference between any of its consecutive terms will be constant
3, 3.25, 3.5, 3.75,
[tex]3.25-3 = 0.25\\\\3.5-3.25 = 0.25\\\\3.75 -3.5 = 0.25[/tex]
The difference between the consecutive terms remains constant so the sequence is arithmetic.
The explicit formula for an arithmetic sequence is:
[tex]a_n = a_1 + d (n-1)[/tex]
Where d is the constant difference between the terms.
[tex]d = 0.25[/tex]
[tex]a_1[/tex] is the first term of the sequence.
[tex]a_1 = 3[/tex]
So
[tex]a_n = 3 +0.25 (n-1)[/tex]
Finally, the recursive formula is:
[tex]a_1 = 3\\\\a_n = a_ {(n-1)} +0.25[/tex]